(untitled) (Patan Pragya, 2021)
In the novel The English Patient, the Sri Lankan-born Canadian writer Michael Ondaatje projects his characters as the diasporic subjects performing their ambivalence regarding identity, culture and nationality. This research article, applying diasporic theories as a critical tool, aims to demonstrate the non-conformist cultural and national stand of the shell-shocked characters at the Italian villa of Girolamo as soon as the devastating Second World War has been over. The novelist Ondaatje and his fictional characters bear the fate of diasporic experience entangled between two cultures. Their divided loyalty demonstrates their fractured subjectivity as an outcome in the colonial and postcolonial setting where they come in contact with the people of the nationality and culture which are different from their own. Cultural mixing is a reality in today’s world resulting from the transnational and cross-border migration. Such a mix-up phenomenon is not creating a one-way-traffic-like influence from the West to the Rest but it is other way round, too.